Determination of Characteristics and Kinetics of Drying Rate of Katuk Leaves (Sauropus androgynus L. Merr) as Herbal Tea with Variations in Temperature and Drying Time - Dewi, Wika Prasetia; Nugrahani, Ratri Ariatmi; Ismiyati; Hendrawati, Tri Yuni (Journal of Applied Sciences and Advanced Technology, 2025)
Katuk is a plant that belongs to the indigenous species that can adapt well in relatively diverse environmental conditions. The following leaves are young shoots used as nutritious food ingredients laktogogum which can increase the amount of breast milk in breastfeeding and warding mothers, the katuk plant can be made into other innovations such as herbal tea.The aim of the study was to determine the effect of drying temperature on the activity of katuk leaf tea. Drying katuk leaf tea is used at temperatures of 40 °C, 50 °C, 60 °C for 1,2,3,4, up to 5 hours. The study used a completely randomized design (CRD) method with 3 treatments and 5 replications in order to obtain 15 experimental units. The data obtained were analyzed by analysis of variance (ANOVA). HThe results of the Two Way ANOVA test at the time of heating show F count = 3.569 and F table = 3.837 so that F count < F table, and at heating temperature shows F count = 38.361 and F table = 4,458 F value > of F crit, it can be concluded that heating time did not have a significant effect while the heating temperature had a significant effect on the water content of katuk leaves. The results showed the water content of 12.093-17.301% so that it still does not meet the requirements set by SNI, namely for the preparation of dry tea it must have a water content of 8% (SNI, 01-3836-2013). Drying rate 0.003-0.02 (g water/g sample.hour). Where the higher the drying rate, the greater the amount evaporated per minute. Ash content 12.22%. Yield 67,567- 98.936%where the greater the total yield value for each temperature and drying time, the more effective and efficient the process for raw materials is. In this study, katuk leaf tea which had the highest yield was dried at 50 oC for 5 hours, with IC50 values between 89 - 7145.6 g / ml. the most found at a drying temperature of 60 oC for 2 hours at 89 g/ml has a very active antioxidant content when compared to temperatures of 40 oC and 50 oC. From the samples tested, the panelists generally liked the katuk leaf tea which was heated at 40 oC for 5 hours.The study of drying rate kinetics resulted in the drying rate constant 2.03 and of the order 0.35.